Evaluation of the effect of Bovis Calculus Artifactus on eight rat liver cytochrome P450 isozymes using LC-MS/MS and cocktail approach. (2nd September 2021) - Zhang, Yun-Jing; Zhou, Wen-Li; Yu, Fei; Wang, Qian; Peng, Can; Kan, Jia-Yi
Abstract: Bovis Calculus Artifactus (BCA) is the main substitute for natural Calculus bovis, a traditional drug in China used to treat high fever, convulsion, and sore throat. The effect of BCA on cytochrome P450 (CYP) activities is unknown. This study was to investigate the effect of BCA on eight rat hepatic microsomal CYPisozymes to evaluate the potential drug interactions using the cocktail approach. Metabolites of the eight isoform probe substrates of CYP isozymes were quantified by LC-MS/MS. The method was validated by incubating known CYP inhibitors α-naphthoflavone (CYP1A2), thiotepa (CYP2B1), quercetin (CYP2C7), sulfaphenazole (CYP2C6), ticlopidine (CYP2C11), quinidine (CYP2D1), ketoconazole (CYP3A1), 4-methylpyrazole (CYP2E1) with individual probe substrate and rat liver microsomes. The formation rates of the corresponding metabolites of the eight probe substrates were determined to evaluate the activity of each isozyme. The results showed that BCA has different degrees of inhibitory effect on four CYP450 isoforms (CYP2C6, CYP2C11, CYP2D1, CYP3A1) ( p  < 0.05), but no significant influence on CYP1A2, 2B1, 2C7 or 2E1 ( p  > 0.05). Attention should be paid to the BCA-drug interactions by careful monitoring and appropriate dosage adjustments in the concurrent use of the drugs which are metabolized by CYP1A2, CYP2C19, and CYP3A4. Abbreviations: BCA, bovis calculus artifactus; CYP, cytochrome P450; DDIs, drug-drug interactions; ESI, electrospray ionization; MRM, multiple reaction monitoring; NBC, Natural Bovis Calculus; QC, quality control; T CM, traditional Chinese medicine.